Linking pathways from perceived absolute and comparative risk to colorectal cancer screening intention: towards an extended Cognitive Mediation Model - Zhang, Thomas H.; Tham, Jen Sern; Lee, Edmund W. J.; Waheed, Moniza (Routledge, 2024)
Digital media platforms are crucial in providing health information to the public, including learning about cancer prevention strategies. Although the Cognitive Mediation Model (CMM) is a sound theoretical framework for explaining the underpinning process of health knowledge acquisition, one important remaining gap is how individuals are motivated to process health information through different discussion-generated elaboration strategies. To better understand the knowledge acquisition process, this paper extends the CMM in the context of colorectal cancer prevention. We introduced perceived absolute risk and perceived comparative risk as two distinct risk assessments as the antecedents facilitating individuals’ attention to cancer information on digital media, two types of interpersonal communication as discussion-generated elaboration strategies, and two dimensions of knowledge assessment in our extended CMM. Based on a nationally representative online survey among 965 Chinese public, we found that two types of risk perception were positively associated with paying attention to colorectal cancer information on digital media, which in turn facilitated both types of interpersonal communication. However, information processing strategies differed in leading to cancer knowledge and screening intention. Only subjective knowledge was positively associated with colorectal screening intention. Our findings offered implications for the literature and health promotion practices. © 2024 Central States Communication Association.